PENGARUH DISIPLIN KERJA, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN UD. AMIK ART GALLERY - Fauziah, Cika Mariska; Suryana, Alean Kistiani Hegy; Hari Purwanto; Unna Ria Safitri; Mohd Shukor Harun (Universitas Boyolali, 2025)
The purpose of this research is to determine the influence between work discipline, compensation, and work environment on employee performance at UD. Amik Art Gallery. In this study using quantitative methods with primary data collection techniques through questionnaires. The population in this study was 62 people and then a saturated sample of 62 respondents was taken. The data is processed using SPSS. The results showed that based on the results of the t hypothesis test, the work discipline variable had a significance value of 0.092 > 0.05 which means that partially the work discipline variable has no effect on employee performance. The compensation variable has a significance value of 0.213 > 0.05 which means that partially the compensation variable has no effect on employee performance. Work environment variables have a significance value of 0.028 < 0.05 which means that partially work environment variables affect employee performance. Based on the F test, a significance value of 0.000 < 0.05 is obtained which means simultaneously the variables of work discipline, compensation and work environment affect employee performance. Keywords: Work Discipline, Compensation, Work Environment, and Employee Performance.